National Law and Minangkabau Customary Law Disparity in Ulayat Land Disputes in the Bidar Alam Area, West Sumatra - Satria, M. Yudi; Anggoro, Purwadi Wahyu; Setiono, Joko (Greenation Publisher & Yayasan Global Resarch National, 2025)
This study critically examines the structural conflict between Indonesia’s positivist legal framework and indigenous ulayat land tenure, using the Bidar Alam case as a focal point. The criminalization of customary land defenders and the continued exploitation of ancestral land by corporations expose the state’s failure to operationalize Article 18B(2) of the 1945 Constitution. Despite formal recognition, customary law remains subordinated through weak legal pluralism, bureaucratic inertia, and epistemological misrecognition. Utilizing a normative juridical method and a conceptual framework rooted in Van Vollenhoven’s adatrecht, John Griffiths’s legal pluralism, and Romli Atmasasmita’s Integrative Legal Theory, this study interrogates the systemic marginalization of masyarakat adat. It advocates for a radical restructuring of Indonesia’s legal architecture beyond symbolic recognition toward substantive justice through dialogical legality. The goal is to harmonize state and customary law by institutionalizing adat practices, strengthening local governance, and embedding indigenous sovereignty within legal mechanisms. This integrative approach is essential for achieving plural, inclusive, and post-colonial agrarian justice.